Delirium after a traumatic brain injury: Predictors and symptom patterns - Maneewong J. (2017)
© 2017 Maneewong et al. Background: Delirium in traumatic brain injury (TBI) is common, may be predictable, and has a multifaceted symptom complex. This study aimed to examine: 1) the sum score of Glasgow Coma Scale (GCS) and if its component scores could predict delirium in TBI patients, and 2) the prominent symptoms and their courses over the first days after TBI. Methods: TBI patients were recruited from neurosurgical ward inpatients. All participants were hospitalized within 24 hours after their TBI. Apart from the sum score of GCS, which was obtained at the emergency department (ED), the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, diagnostic criteria for delirium were applied daily. The severity of delirium symptoms was assessed daily using the Delirium Rating Scale – Revised-98 (DRS-R-98). Results: The participants were 54 TBI patients with a mean GCS score of 12.7 (standard deviation [SD] =2.9). A total of 25 patients (46.3%) met the diagnosis of delirium and had a mean age of 36.7 years (SD =14.8). Compared with 29 non-delirious patients, 25 delirious patients had a significantly lower mean GCS score (P=0.04), especially a significantly lower verbal component score (P=0.03). Among 18 delirious patients, four symptoms of the DRS-R-98 cognitive domain (orientation, attention, long-term memory, and visuospatial ability) were moderate symptoms (score ≥2) at the first day of admission. After follow-up, three cognitive (orientation, attention, and visuospatial ability) and two noncognitive symptoms (lability of affect and motor agitation) rapidly resolved. Conclusion: Almost half of patients with mild to moderate head injuries may develop delirium in the first 4 days after TBI. Those having a low GCS score, especially the verbal component score, at the ED were likely to have delirium in this period. Most cognitive domains of delirium described in the DRS-R-98 were prominent within the first 4 days of TBI with delirium. Three cognitive and two noncognitive symptoms of delirium decreased significantly.